PENGADAAN MAGRIB MENGAJI SEBAGAI KEGIATAN REMAJA MASJID RW 05 DESA KEDUNGDAWA DALAM UPAYA MENUMBUHKAN JIWA DAKWAH DI MASJID AL-MUHAJIRIN: PENGADAAN MAGRIB MENGAJI SEBAGAI KEGIATAN REMAJA MASJID RW 05 DESA KEDUNGDAWA DALAM UPAYA MENUMBUHKAN JIWA DAKWAH DI MASJID AL-MUHAJIRIN - abdurrahman; Moh Sugiono; Siska; Sepnalisa; Duriyah (UI Cirebon (Universitas Islam Cirebon), 2023)
Potential development is the hope and goal of everyone who has known his potential. However, if the potential has not been realized, then someone will have difficulty and don't even know what to do. With innovative monitoring and observation and with innovative research, it is hoped that everyone will be able to know their potential. Because everyone is a component that is very influential on the environment, both in society, economic activities, even in the development of the revival of an area. Youth is the strongest element in society, especially youth who are educated and principled and active in all positive activities. Through innovative research, it is hoped that every youth and generally every element of society is aware of their potential so that the development stage will be faster. Especially the youth who are members of the Youth Mosque activities. With great potential, it is also hoped that a massive positive impact will soon be felt by the entire village community, generally felt by the entire Indonesian nation. One of the potentials that must be developed by every individual Muslim is the soul of proselytizing because every individual Muslim is required to become a da'i.Because ten youths are enough to shake the world, one young man is able to shake a country.